PENYALURAN ZAKAT UNTUK TUJUAN PRODUKTIF BAGI PEMBERDAYAAN UMKM: TINJAUAN PUSTAKA SISTEMATIS - Trimulato; Asyraf Mustamin; Syarifuddin (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2026)
This study explores the distribution of zakat for productive purposes to empower Micro, Small, and Medium Enterprises (MSMEs). The research addresses the growing need for effective zakat management to enhance economic empowerment in the Muslim community. The primary objective is to analyze existing literature on productive zakat and its impact on MSMEs using a systematic literature review (SLR) methodology. Data were collected using Publish or Perish and subsequently analyzed in VOSviewer to visualize research trends, keyword networks, and collaboration patterns. The findings reveal that zakat distribution is increasingly focused on economic empowerment, with Indonesia emerging as a significant case study due to its substantial zakat potential. Key themes identified include the effectiveness of zakat in fostering MSME productivity and sustainability. The study highlights gaps in current research, particularly concerning implementing zakat in diverse economic contexts. Policy implications suggest the need for enhanced zakat management frameworks and multisectoral collaboration to optimize zakat's role in economic development.